Новый вид лептотромбидий - Leptotrombidiumsilvaticum sp. n. (Acariformes, Trombiculidae) - Гуща, Г.И.; Шлугер, Е.Г. (Вестник зоологии, 1967)
A new species of trombiculid mites Leptotrotnbidiurn siloaticurn sp. n. is described. The new species differs from the nearly related species Leptotrombidium intermedium europaeum Daniel et Breli h, 1959, in the formula of dorsal setae — 2-8-6-6...., in the smaller dimensions of the scutum and in the arrangement of the palpal tarsi.